An Innovative Setup to Investigate High-temperature and High-stress Flow Properties for Industrial Processes Particles - Salvatore La Manna; Sina Zinatlou Ajabshir; Diego Barletta; Massimo Poletto (Chemical Engineering Transactions)
The study of the sliding properties of coarse particles faces significant limitations in terms of the equipment developed and the theoretical frameworks employed. These limitations become even more critical when considering variables such as control of the reactant atmosphere, high temperatures and high-stress conditions. Understanding the flow property and the ability of a material to move freely without creating obstructions is crucial in various industries, including steel production. During the synthesis process, pellets containing oxidised forms of iron undergo gravity flow and progressive remelting to produce metal pellets. In the reduction phase, harsh conditions induce phenomena such as fragmentation, softening, cohesion, and changes in surface properties, all of which can hinder the natural movement of particles. Therefore, it is essential to replicate these process conditions on a laboratory scale to comprehend how these phenomena adversely affect material flow properties. To address this need, an experimental setup capable of simulating harsh process conditions and accurately quantifying parameters to characterise particle flow properties was developed. The validity of the new setup was confirmed by comparing data obtained from it and traditional equipment using sand as a reference material. The consistency of the results validates the quality of the data obtained, highlighting the potential and reliability of the new apparatus, with the intention of extending this potential to fields of industrial interest.